Viabilitas (Ketahanan) Lactobacillus acidophilus Dalam Pakan Ayam Broiler Untuk Menghambat Penyakit Pullorum - Ida Ningrumsari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The pullorum disease is known by the name of defecating chalk or white defecation (Bacilary white Diarrchae) which causes a lot of losses for breeders, therefore conducted research with the aim to know the resilience (viability) L acidophilus in broiler chicken feed with the aim to inhibit pullorum disease. The research design uses laboratory experimental, quadratic equations and Completely Randomized Design (RAL) 1 factorial with L acidophilus concentration of 106-109. Pre-study observed the best growth curve of L acidophilus, the results showed that at 12 hours, the results of this study were used to inhibit Salmonella pullorum, while the best growth curve of S pullorum that can infect the chickens is at the age of 15 hours. For L acidophilus concentrations which can inhibit S pullorum done in vitro ie at concentration 107, LD50 Salmonella pullorum in vivo broiler on 108. Viability of L acidophilus in feed can survive above 35 days.